Changes in Culinary Culture among Ukrainians Living in the USA in the Second Half of the 20th – Early 21st Century and Their Role in Preservation of the National Identity - Olena Braichenko (Українознавство, 2019)
The article examines the culinary section in Nashe Zhyttia (Our Life) magazine published by the Ukrainian National Women’s League of America from 1944 to 2016, as well as other materials of the magazine (e.g., opinion pieces, travel articles, memoirs, letters to the editor), all of which, in one way or another, relate to food and the culinary culture of Americans with the Ukrainian roots. Nashe Zhyttia magazine targets the female audience, focusing on preserving national identity, professional development of women, and current issues. These materials reflect topical concerns of the global Ukrainian community; the role and status of the woman in a family, at her workplace, and in the society; dietary habits and culinary innovations. It uncovers the vital role of the national cuisine in preserving and promoting the ethnic identity in a multicultural setting. It brings to light the development of the Ukrainian cuisine in the US society (e.g., cultural, ethnic, economic, and environmental). A careful study of the culinary articles helps understand the pressing issues of preserving, adjusting, and developing Ukrainian cuisine in the second half of the 20th century and the beginning of the 21st century. It is established that awareness of the Ukrainian culinary traditions, knowledge of the ritual dishes recipes have served for decades as a means of preserving ethnic cohesion and creating a sense of belonging to the Ukrainian community. According to the research, local American food, national holidays, culinary fashion, and the different systems of weights and measures existing in the US and Ukraine affected the culinary traditions of Americans of Ukrainian descent, impacting the development of Ukrainian cuisine in America. The organizational activities of the Ukrainian National Women’s League of America helped elucidate changes in the culinary behavior, views on wholesome food and junk food, dinner etiquette and hosting. A separate discussion is devoted to the subject of ritual dishes and their importance in the lives of contemporary Ukrainian Americans, as well as the potential of the Ukrainian cuisine to serve as a Ukrainian trademark.